PENGELOLAAN PEMBELAJARAN IPA BIOLOGI DI MTs ASSALAM KRANGGAN TEMANGGUNG - PRANOTO , BEJO (2011)
Research purposes to (1) describe Biology's Science learning planning in MTs Assalam of Kranggan Temanggung. (2) describe Biology's Science learning execution in MTs Assalam Kranggan Temanggung. (3) describe Biology's Science learning evaluation in MTs Assalam Kranggan Temanggung Research done in MTs Assalam Kranggan Temanggung, Secang-Temanggung street, Kranggan Temanggung sub district. Research technique using qualitative analysis technique. Data gathering technique done by observation, interview and dokumentatian. Research results are : (1) Science Learning execution planning done by teachers in Biology's Science bassed on Subject Discusion Temanggung Sub district, (2) Learning execution done by using variation learning mode oriented to students active, which can improve learning efectiveners, solving impase mind, and improving appreciation of difference in a group,(3) Biology's Science learning evaluation with variatif learning method done in MTs Assalam Kranggan Temanggung, done orally and also written for some students. It was done in process and learnig result to know students ability; interest, attention and study motivation ; study attitude; basic knowledge and prerequisite; and characteristic